G439(P) It's time to standardise the duration of antibiotics for suspected early onset neonatal sepsis. (May 2019) - Devlin, H; Narendra, D; Malley, M
Abstract : Aims: National antibiotic practice in cases of suspected early onset neonatal sepsis (EONS) is varied. NICE recommend antibiotic cessation at 36 hours with negative cultures for low-risk asymptomatic babies with negative CRPs. We modelled the impact of switching to a 36 hour culture threshold (from 48 hours) at our unit and extrapolated this nationally. Methods: We contacted all 155 neonatal units in England by phone to assess current national antibiotic practice. We retrospectively identified 463 neonates treated for suspected EONS at our level 1 unit. Reviewing investigation results and clinical information, we assessed which babies met NICE criteria to stop antibiotics at 36 hours. We calculated the expected savings in terms of staff time, bed-days and antibiotic doses and extrapolated this nationally. Results: 91 units reported using a 36 hour blood culture threshold. 59 units (38%) reported awaiting 48 hour cultures, with 2 35 972 babies born in these units in 2016–17. Five units awaited 24 hour cultures. At our unit, 45.1% of screened babies were found to satisfy NICE Criteria for antibiotic cessation at 36 hours. Despite this, the average antibiotic course in these babies was 56 hours due to the delay in culture availability. Stopping antibiotics at 36 hours in these babies would have saved 502 antibiotic doses over 8 months, with 53.6 nursing hours redirected to other activities. On reviewing clinical information 33% of all screened babies were fit for discharge at 36 hours and were only awaiting cultures; thus 147 families could have returned home at least 12 hours earlier. NICE guidelines suggest 10% of babies are screened for sepsis nationally. Extrapolating our unit's figures suggests 25 505 antibiotic doses could be saved annually if all units stopped antibiotics according to NICE criteria at 36 hours. 7787 babies could go home earlier to their families, saving 3893.5 bed days and 2838 nursing hours from antibiotic administration. Conclusion: A clinical and business case can be made for all units to follow NICE guidelines and stop antibiotics at 36 hours in low-risk asymptomatic babies treated for EONS. Less quantifiable impacts include prevention of antibiotic resistance, gentamicin toxicity and re-cannulation events, as well as improving patient satisfaction and staff morale.